EFFECTIVENESS OF SURGICAL PREVENTION OF POSTOPERATIVE PURULENT COMPLICATIONS IN CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Postoperative purulent complications (POC) remain one of the significant problems in pediatric surgery, since they can significantly worsen the outcomes of surgical interventions and increase the duration of recovery. In children, due to the peculiarities of the immune system and anatomical and physiological characteristics, the risk of developing such complications may be higher than in adults, which requires a special approach to prevention and treatment [7, 13, 2].